2008
DOI: 10.3168/jds.2007-0231
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Prediction of Gene Content in Large Animal Populations and its Use for Candidate Gene Detection and Genetic Evaluation

Abstract: To estimate and to use the effects of single genes on quantitative traits, genotypes need to be known. However, in large animal populations, the majority of animals are not genotyped. These missing genotypes have to be estimated. However, currently used methods are impractical for large pedigrees. An alternative method to estimate missing gene content, defined as the number of copies of a particular allele, was recently developed. In this study, the proposed method was tested by assessing its accuracy in estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…These results confirm the tendencies reported by Gengler et al (2008) and Waters et al (2011). Therefore, the tyrosine allele could be useful in selection to improve resistance to mastitis.…”
Section: Discussionsupporting
confidence: 91%
“…These results confirm the tendencies reported by Gengler et al (2008) and Waters et al (2011). Therefore, the tyrosine allele could be useful in selection to improve resistance to mastitis.…”
Section: Discussionsupporting
confidence: 91%
“…Gengler et al (2007) reported also very similar correlations between true and predicted gene contents using either the S-MM or SIP. Allele substitution effects were overestimated in agreement with Gengler et al (2008), but in disagreement with Baruch and Weller (2009), who found that allele substitution effects were underestimated. Clearly, the overestimation is partly due to genotyping only a selected group of sires in generations 1 to 4 (see Table 6), whereas Baruch and Weller (2009) genotyped all bulls in each generation.…”
Section: Methods and Resultsmentioning
confidence: 55%
“…Several methods exist to impute missing genotypes that, apart from the genotypic information at the locus of interest, use only pedigree data (Gengler et al, 2007(Gengler et al, , 2008, only surrounding markers (EastPHASE; Scheet and Stephens, 2006), or both (Li and Jiang, 2003;Kong et al, 2008;Meuwissen and Coddard, 2010;Mulder et al, 2010b). The mixed model (BLUP) method presented by Gengler et al (2007) uses the BLUP framework to derive missing gene content conditional on genotypic information of relatives.…”
Section: Introductionmentioning
confidence: 99%